2020
DOI: 10.1093/femsre/fuaa018
|View full text |Cite|
|
Sign up to set email alerts
|

The multifarious roles of Tol-Pal in Gram-negative bacteria

Abstract: In the 1960s several groups reported the isolation and preliminary genetic mapping of Escherichia coli strains tolerant towards the action of colicins. These pioneering studies kick-started two new fields in bacteriology; one centred on how bacteriocins like colicins exploit the Tol (or more commonly Tol-Pal) system to kill bacteria, the other on the physiological role of this cell envelope-spanning assembly. The following half century has seen significant advances in the first of these fields whereas the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 159 publications
(264 reference statements)
3
69
0
Order By: Relevance
“…TolR and pal are two genes of the Tol-Pal system, and the transposon insertion of tolR and pal showed 8.8-and 10.6-fold decreased prodigiosin production, respectively. The Tol-Pal system plays important roles in cell division and phospholipid transport from the membrane of bacteria (Szczepaniak et al, 2020). It was found that different kinds of oils can significantly enhance prodigiosin production of many strains in the Serratia genus (Wei and Chen, 2005;Abdul Manas et al, 2020), including the S. marcescens FZSF02 strain, which was used in this study (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TolR and pal are two genes of the Tol-Pal system, and the transposon insertion of tolR and pal showed 8.8-and 10.6-fold decreased prodigiosin production, respectively. The Tol-Pal system plays important roles in cell division and phospholipid transport from the membrane of bacteria (Szczepaniak et al, 2020). It was found that different kinds of oils can significantly enhance prodigiosin production of many strains in the Serratia genus (Wei and Chen, 2005;Abdul Manas et al, 2020), including the S. marcescens FZSF02 strain, which was used in this study (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…S3), which plays essential roles in the stabilization of the outer membrane structure and septum formation during cell division. Additionary, ybgC, whose relevance to the Tol-Pal system is unknown, was found immediately upstream of exbB2/tolQ 19,28 . Since a similar set of genes (ybgC-tolQ-tolR-tolA-tolB-pal) has been found in many bacteria as the genes encoding the Tol-Pal system 29 , exbB2/tolQ and exbD3/tolR are likely components of the Tol-Pal system.…”
Section: Resultsmentioning
confidence: 99%
“…Their import is driven by the proton-motive force (PMF) in conjunction with either the Tol (group A bacteriocins) or the Ton (group B bacteriocins) systems 8 . The physiological roles of the Tol (also known as Tol-Pal) and Ton systems are to stabilise the OM during cell division 9 and transport nutrients through TonB-dependent transporters (TBDTs) 10 , respectively. These functions are parasitized by bacteriocins to catalyse their transfer across the OM.…”
Section: Introductionmentioning
confidence: 99%